Down-regulation of endogenes mediated by a transitive silencing signal - Bleys, Annick (Cold Spring Harbor Laboratory Press, 2006)
Some RNA silencing systems in plants, nematodes, and fungi show spreading of silencing along target sequences, termed transitive silencing. Here, we address the question of whether endogenous targets can be silenced by a transitive silencing signal in plants. In transgenic Arabidopsis thaliana plants that harbored a silencing-inducing locus and a transgenic chimeric primary target, silencing of a secondary transgenic target occurred and the expression of the endogenous catalase genes was down-regulated, coinciding with a knock-down phenotype. Strikingly, the efficiency of the catalase silencing appeared to be correlated with the zygosity of the primary target locus and, to a lesser extent, with that of the silencing-inducing locus. These data suggest that silencing of an endogene induced by transgenic secondary small interfering RNAs (siRNAs) might depend on the amount of primary target transcripts that can act as template for the production of an efficient transitive silencing signal.